Estudio Jurídico Doctrinario del derecho a la Identidad respecto a la Posesión Notoria del Apellido en Adolescentes” - Maldonado Calderón, Adriana Stefanía (2023)
The present research project entitled "Estudio Jurídico Doctrinal del Derecho a la Identidad” regarding the Notorious Possession of the surname in adolescents" deals with the realization of a legal-doctrinal study of the right to identity that, although it is true our "Magna Carta" through This right includes the free choice of surnames, a right empowered for adolescents. Since the Constitution allows free choice, it empowers the adolescent to carry out the procedure through which there is a personal choice of the surnames with which the people identify themselves before society. This faculty can be carried out through the figure of notorious possession that determines that to carry out the procedure to change the surname in adolescents, the person must have known possession of the surnames with which they wish to identify these different from those that appear in their legal documents. The procedure under analysis involves allowing the adolescent to exercise the right to identity, the problem lies in the impossibility demonstrated in many cases where the exercise of this right becomes impossible due to the time in which it is required to have notorious possession of the surname since this period being so long of 10 years it becomes impossible configuration and compliance, by not being able to justify this normative precept for so long, thus violating the exercise of the right to identity in adolescents, in addition to considering this possession notorious for the time prohibited by forcing the adolescent to carry a double identity or one identity fictitious by not providing it with the necessary weapons to be able to carry out compliance with this temporary requirement. Therefore, it is necessary to point out that this project is framed in the possibility of providing protection to the adolescent so that they exercise in a factual and practicable manner the right to identity, through the change of surnames due to notorious possession, and even protect the adolescent from others types of violations considering that not only is this right violated, but since it is the main one violated, other rights are violated at the same time, such as the right to comprehensive development, the right to ensure the best interests of the child, the right to education , right to freedom, free development of personality and the right to mental health, also principles such as effectiveness, procedural speed, and procedural economy. As we can see, the analysis of this project is of great significance towards the protection of the rights of adolescents.